The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ijc.28056
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐182 and miR‐203 induce mesenchymal to epithelial transition and self‐sufficiency of growth signals via repressing SNAI2 in prostate cells

Abstract: MicroRNAs play critical roles in tumorigenesis and metastasis. Here, we report the dual functions of miR-182 and miR-203 in our previously described prostate cell model. MiR-182 and miR-203 were completely repressed during epithelial to mesenchymal transition (EMT) from prostate epithelial EP156T cells to the progeny mesenchymal nontransformed EPT1 cells. Re-expression of miR-182 or miR-203 in EPT1 cells and prostate cancer PC3 cells induced mesenchymal to epithelial transition (MET) features. Simultaneously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…In cancer metastasis, EMT is a key process that converts polarized immotile epithelial cells into motile invasive mesenchymal cells, which subsequently enables cancer cells to acquire stem cell characteristics and aggressive malignant properties [34,35]. MiR-203 has been shown to directly suppress EMT activators such as ZEB2 and SNAI1/2 in various types of cancer [32,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer metastasis, EMT is a key process that converts polarized immotile epithelial cells into motile invasive mesenchymal cells, which subsequently enables cancer cells to acquire stem cell characteristics and aggressive malignant properties [34,35]. MiR-203 has been shown to directly suppress EMT activators such as ZEB2 and SNAI1/2 in various types of cancer [32,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, miR-182 promotes cellular differentiation and mesenchymal to epithelial transition, by regulating the expression of the transcription factor SNAI2. 48 In summary, these and many additional studies identified miR-182 as a critcal factor that controls cell fate specification and cell differentiation during development through targeting of a diverse network of developmental genes. 49,50 In vivo miRNA delivery for GBM therapy…”
Section: Mir-182 Expression Influences Multiple Tumor Biological Propmentioning
confidence: 90%
“…During the embryonic stages of development, miR-182 levels are low but significantly increase postnatally, suggesting a role for miR-182 in terminal differentiation of retinal progenitor cells and maintenance of mature retinal neuron function (Xu et al 2007). Several other recent studies have suggested that miR-182 promotes cellular differentiation by regulating the expression of the transcription factor SNAI2 and induces mesenchymal-to-epithelial transition (Qu et al 2013). Consistent with these findings, we demonstrate that miR-182 overexpression in GICs reduces sphere size and expansion and promotes differentiation along neuronal and astroglial axes at least in part via targeting of c-Met and HIF2A signaling.…”
Section: Discussionmentioning
confidence: 99%